Relationship between Nurses' Knowledge and Attitudes toward Patient Safety Culture Implementation in Inpatient Wards: A Cross-Sectional Study at Mitra Sejati Hospital - Ruminta Sirait; Grace Mutiara (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background and Purpose: Adverse events in hospitals remain a persistent global patient safety challenge, with nurses' knowledge and attitudes identified as key determinants of safety culture quality. This study aimed to investigate the relationship between nurses' knowledge and attitudes toward patient safety and the implementation of patient safety culture in inpatient wards of Mitra Sejati General Hospital, Medan, Indonesia. Methods: A cross-sectional correlational study was conducted among 85 inpatient ward nurses recruited via total sampling. Inclusion criteria included nurses actively serving in inpatient wards for >= 6 months who consented to participate; nurses on administrative leave or student nurses were excluded. Data were collected using three validated instruments: a 30-item patient safety knowledge questionnaire (Cronbach's alpha = 0.83), a 25-item attitude scale (Cronbach's alpha = 0.81), and the Hospital Survey on Patient Safety Culture version 2.0 (HSOPSC v2.0; Cronbach's alpha = 0.87). Data were collected from September 1 to October 31, 2025. Ethical clearance was obtained from the Health Research Ethics Committee, Universitas Sumatera Utara (No. 451/TGL/KEPK FK USU/2025). Spearman rank correlation and multiple linear regression analysis were performed using SPSS version 26 (alpha = 0.05). Results: The majority of participants were female (69.4%), aged 31-40 years (43.5%), and had completed Bachelor of Nursing education (52.9%). Patient safety knowledge was predominantly in the adequate category (41.2%), with mean 72.4 +/- 11.8. Attitudes were predominantly positive (61.2%), with mean 74.6 +/- 9.3. Patient safety culture implementation was mostly in the adequate category (52.9%), with mean 71.8 +/- 10.5. Significant positive correlations were found between knowledge and PSC implementation (rs = 0.524; p < 0.001) and between attitude and PSC implementation (rs = 0.612; p < 0.001). Multiple regression revealed that both variables together explained 44.1% of variance in PSC implementation (R2 = 0.441; F = 32.33; p < 0.001). Conclusion: Both nurses' knowledge and attitudes toward patient safety are significantly associated with the implementation of patient safety culture. Attitude demonstrated a stronger association than knowledge. Hospital management should prioritize routine patient safety training and a culture-building approach to strengthen both cognitive and attitudinal dimensions of patient safety among inpatient nurses.